A Catalog of Human Genes Associated With Pathozoospermia and Functional Characteristics of These Genes - Ignatieva, Elena V.; Osadchuk, Alexander V.; Kleshchev, Maxim A.; Bogomolov, Anton G.; Osadchuk, Ludmila V. (Frontiers in Genetics, 2021)
Genetic causes of the global decline in male fertility are among the hot spots of scientific research in reproductive genetics. The most common way to evaluate male fertility in clinical trials is to determine semen quality. Lower semen quality is very often accompanied by subfertility or infertility, occurs in many diseases and can be caused by many factors, including genetic ones. The following forms of lowered semen quality (patozoospermia) are known: azoospermia, oligozoospermia, asthenozoospermia, teratozoospermia, and some combined forms. To systematize information about the genetic basis of impaired spermatogenesis, we created a catalog of human genes associated with lowered semen quality (HGAPat) and analyzed their functional characteristics. The catalog comprises data on 126 human genes. Each entry of the catalog describes an association between an allelic variant of the gene and a particular form of lowered semen quality, extracted from the experimental study. Most genes included into the catalog are located on autosomes and are associated with such pathologies as nonobstructive azoospermia, oligozoospermia or asthenozoospermia. Slightly less than half of the included genes (43%) are expressed in the testes in a tissue-specific manner. Functional annotation of genes from the catalog showed that spermatogenic failure can be associated with mutations in genes that control biological processes essential for spermiogenesis (regulating DNA metabolism, cell division, formation of cellular structures, which provide cell movement) as well as with mutations in genes that control cellular responses to unfavorable conditions (stress factors, including oxidative stress and exposure to toxins).